Effect of Extended π‐Conjugation Structure of Donor–Acceptor Conjugated Copolymers on the Photoelectronic Properties. Issue 10 (8th August 2014) - Wang, Meng; Shi, Shaowei; Ma, Di; Shi, Keli; Gao, Chen; Wang, Liwei; Yu, Gui; Li, Yongfang; Li, Xiaoyu; Wang, Haiqiao
Abstract New donor–acceptor conjugated copolymers based on alkylthienylbenzodithiophene (BDTT) and alkoxynaphthodithiophene (NDT) have been synthesized and compared with their benzo[1, 2‐b:4, 5‐b′]dithiophene (BDT)‐based analogues to investigate the effect of the extended π conjugation of the polymer main chain on the physicochemical properties of the polymers. A systematic investigation into the optical properties, energy levels, field‐effect transistor characteristics, and photovoltaic characteristics of these polymers was conducted. Both polymers demonstrated enhanced photovoltaic performance and increased hole mobility compared with the BDT‐based analogue. However, the BDTT‐based polymer (with π‐conjugation extension perpendicular to main chain) gave the highest power conversion efficiency of 5.07 % for the single‐junction polymer solar cell, whereas the NDT‐based polymer (with π‐conjugation extension along the main chain) achieved the highest hole mobility of approximately 0.1 cm2 V−1 s−1 based on the field‐effect transistor; this indicated that extending the π conjugation in different orientations would have a significant influence on the properties of the resulting polymers.